Bivalvia (Mollusca) de la Formación San Juan (Ordovícico Temprano, Precordillera argentina) (Ameghiniana, 2014)
Bivalves are described from early Ordovician limestones of Precordillera basin for the first time. The collection includes the families Modiolopsidae (Modiolopsis? sp.) and Ambonychiidae, which is represented only by a single undetermined genus. Because fossiliferous levels are early Arenig in age, the specimen of ambonychiid represents the oldest known record of the family.